2020
DOI: 10.1080/14786419.2020.1837824
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti-trypanosomal potential of kaurane and pimarane semi-synthetic derivatives

Abstract: As part of the search for anti-trypanosomal agents, this work presents the production of sixteen derivatives. All of them were obtained from two natural diterpenes, one with kaurane skeleton (ent-kaurenoic acid) and other with a pimarane skeleton (entpimaradienoic acid). Then, the eighteen compounds were assayed against epimastigote form of Trypanosoma cruzi, with the derivatives showing increase of activity in relation to their precursors. Moreover, the most active derivative presented an IC50 <12,5 M (estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A trypanocidal activity research of pimarane diterpenes isolated from Aldama arenaria described the activity of the ent- 15-pimarene-8ß,19-diol (131) with IC 50 of 116.5 ± 1.21 µM while that of the positive control, gentian violet, was 76 µM (Ambrosio et al 2008). In other study ent-pimaradienoic acid (127) showed in-vitro trypanocidal activity with IC 50 of 68.7 µM (reference compound: benznidazole, IC 50 = 9.8 ± 0.68 µM), and the activity improved by esterification (Rocha et al 2022). In vitro studies against T. cruzi identified the activity of compounds 151, 171, and 187 isolated from Aldama aspilioides (Da Costa et al 1996a).…”
Section: Resultsmentioning
confidence: 90%
“…A trypanocidal activity research of pimarane diterpenes isolated from Aldama arenaria described the activity of the ent- 15-pimarene-8ß,19-diol (131) with IC 50 of 116.5 ± 1.21 µM while that of the positive control, gentian violet, was 76 µM (Ambrosio et al 2008). In other study ent-pimaradienoic acid (127) showed in-vitro trypanocidal activity with IC 50 of 68.7 µM (reference compound: benznidazole, IC 50 = 9.8 ± 0.68 µM), and the activity improved by esterification (Rocha et al 2022). In vitro studies against T. cruzi identified the activity of compounds 151, 171, and 187 isolated from Aldama aspilioides (Da Costa et al 1996a).…”
Section: Resultsmentioning
confidence: 90%
“…Regarding the ent-pimaradienoic acid ( 91 , IC 50 68.7 μM) set, compound 94 (IC 50 3.8 μM) was the most active against trypomastigotes forms of T. cruzi . However, due to the lack of cytotoxicity data it is not possible to determine the selectivity index of these compounds [ 85 ].…”
Section: Terpenic Compounds With Antitrypanosomal Activitymentioning
confidence: 99%